How do frontline staff use patient experience data for service improvement? Findings from an ethnographic case study evaluation. Issue 3 (July 2020) - Locock, Louise; Montgomery, Catherine; Parkin, Stephen; Chisholm, Alison; Bostock, Jennifer; Dopson, Sue; Gager, Melanie; Gibbons, Elizabeth; Graham, Chris; King, Jenny; Martin, Angela; Powell, John; et al.
Objectives: Improving patient experience is widely regarded as a key component of health care quality. However, while a considerable amount of data are collected about patient experience, there are concerns this information is not always used to improve care. This study explored whether and how frontline staff use patient experience data for service improvement. Methods: We conducted a year-long ethnographic case study evaluation, including 299 hours of observations and 95 interviews, of how frontline staff in six medical wards at different hospital sites in the United Kingdom used patient experience data for improvement. Results: In every site, staff undertook quality improvement projects using a range of data sources. Teams of health care practitioners and ancillary staff engaged collectively in a process of sense-making using formal and informal sources of patient experience data. While survey data were popular, 'soft' intelligence – such as patients' stories, informal comments and observations – also informed staff's improvement plans, without always being recognized as data. Teams with staff from different professional backgrounds and grades tended to make more progress than less diverse teams, being able to draw on a wider net of practical, organizational and social resources, support and skills, which we describe as team-based capital. Conclusions: Organizational recognition, or rejection, of specific forms of patient experience intelligence as 'data' affects whether staff feel the data are actionable. Teams combining a diverse range of staff generated higher levels of 'team-based capital' for quality improvement than those adopting a single disciplinary approach. This may be a key mechanism for achieving person-centred improvement in health care.